2015
DOI: 10.1109/jstars.2015.2407365
|View full text |Cite
|
Sign up to set email alerts
|

Development of Line-of-Sight Digital Surface Model for Co-Registering Off-Nadir VHR Satellite Imagery With Elevation Data

Abstract: Co-registration of very-high-resolution (VHR) images with elevation data is extremely important for many remote sensing applications due to the complementary properties of these two data types. However, this type of multidata source registration has many associated challenges. For instance, although VHR satellite images are usually acquired off-nadir, the integration of off-nadir images with digital surface models (DSMs) for the purpose of urban mapping has been rarely seen in research publications. This is du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…These measures are described and used in Suliman and Zhang (2015). Based on these measures, the overall quality measure was found to be more than 90% relative to manually generated reference data.…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These measures are described and used in Suliman and Zhang (2015). Based on these measures, the overall quality measure was found to be more than 90% relative to manually generated reference data.…”
Section: Data and Resultsmentioning
confidence: 99%
“…The co-registering methods of image and elevation data are extensively reviewed in our previous work (Suliman and Zhang 2015). In that work, we introduced the line-of-sight DSM (LoS-DSM) solution to overcome most of the limitations in the reviewed methods and provide pixel-by-pixel co-registration.…”
Section: Introductionmentioning
confidence: 99%
“…Then, terrain slopes and building heights extracted from a DSM are used to improve built-up area results obtained by using planar features extracted from a DOM [12,39]. The built-up area identification results cannot be superimposed on the raw stereo imagery for display during evaluation [40][41][42]. These methods do not take full advantage of images with different viewing angles of stereo imagery, since these images are only used to produce DSMs and DOMs.…”
Section: Built-up Area Detection Methods Using Height Informationmentioning
confidence: 99%
“…Object-based approaches are usually used to facilitate the integration and reduce the negative effect of the misregistration by changing the processing unit from individual pixels to a group of pixels (i.e., image segments/objects) [7]. Even so, this misregistration problem is still serious for tall buildings appearing in off-nadir VHR images [8].…”
Section: Introductionmentioning
confidence: 99%
“…As found in the literature, this co-registration can be achieved by four different ways: image-to-image registration, orthorectification, true-orthorectification, and the line-of-sight DSM (LoS-DSM) solution. All of these methods are defined, explained and reviewed extensively in [8]. Except for the LoS-DSM co-registration solution, it has been concluded that all of these methods have some limitations when off-nadir images acquired over dense urban environments are employed.…”
Section: Introductionmentioning
confidence: 99%